Isolation and identification of antioxidant phenylpropanoids from the fruit peel of Akebia trifoliata koidz - Kadowaki, Wataru; Sugahara, Yuki; Toyoizumi, Tomoyasu; Nakajima, Teruko; Kumazawa, Shigenori (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2023)
In the course of screening for antioxidant agricultural products in Shizuoka Prefecture, Japan, we found that Akebia trifoliata Koidz fruit had a high activity. Furthermore, we found that the peel of A. trifoliata showed remarkable antioxidant activity compared to other parts of the fruit. We isolated seven known phenylpropanoids, including caffeoylquinic acids from the peel of A. trifoliata: 5-O-caffeoylquinic acid (1), 4-O-caffeoylquinic acid (2), 3-O-caffeoylquinic acid (3), 4,5-di-O-caffeoylquinic acid (4), 3,5-di-O-caffeoylquinic acid (5), calceolarioside B (6), and (4-hydroxyphenyl)-ethyl-6-O-(E)-caffeoyl-β- d -glucopyranoside (7). These isolated compounds were found to contribute to the antioxidant activity of the peel, with 6 exhibiting the strongest activity amongst them. Quantitative analyses showed that 6 is abundant in the peel of A. trifoliata. Therefore, the peel of A. trifoliata can be effectively used as a functional material with antioxidant activity.